Labour Migration and the Swedish Labour Market Model: a case study of recruitment of Yugoslav workers to Svenska Flaktfabriken in Vaxjo, 1969-1970. - Svanberg, Johan (Scandinavian Journal of History, 2011)
This essay deals with active labour recruitment from Yugoslavia to Sweden at the end of the 1960s and early 1970s. It is a case study of recruitments of foreign-born workers to one particular manufacturing industry. It focuses primarily on trade-union actions and strategies in connection with the recruitments, analysed in the light of the power relations within the corporatist Swedish labour market model. This approach illuminates how the Swedish labour market model dealt with an issue involving both conflicting and coincident interests between labour and capital, with the state as an intermediary. But the recruitments are also analysed from the recruited workers' points of view. The essay reveals great union influence in the process of labour recruitment, and suggests that the national Swedish labour market authority only approved as many work permits for non-Nordic workers as the trade union concerned accepted. This power, in combination with the shortage of workers, could be used by the unions as a forceful instrument in their struggle to transform working life according to their members' interests. Accordingly, the labour recruitments to Sweden were framed by the power relations and the corporative practices within the Swedish labour market model.